2016
DOI: 10.1016/j.geothermics.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of heat extraction from variably fractured porous media in Enhanced Geothermal Systems

Abstract: Modeling of heat extraction in Enhanced Geothermal Systems is presented. The study builds on recent studies on the use of directional wells to improve heat transfer between doublet injection and production wells. The current study focuses on the influence of fracture orientation on production temperature in deep low permeability geothermal systems, and the effects of directional drilling and separation distance between boreholes on heat extraction. The modeling results indicate that fracture orientation with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…When the matrix grid is small enough, the pore pressure of the grid can be accelerated to equal the fluid pressure in the NF. 39,45 As fracturing time increases, fluid pressure in the reservoir and in NFs continues to rise. When its value is greater than the normal stress of the NF surface, tensile failure occurs to the NF, that is as follows:…”
Section: Rock Failure Criterionmentioning
confidence: 99%
“…When the matrix grid is small enough, the pore pressure of the grid can be accelerated to equal the fluid pressure in the NF. 39,45 As fracturing time increases, fluid pressure in the reservoir and in NFs continues to rise. When its value is greater than the normal stress of the NF surface, tensile failure occurs to the NF, that is as follows:…”
Section: Rock Failure Criterionmentioning
confidence: 99%
“…Investigations into EGS for electricity production are underway in Canada and abroad, e.g. (Ferguson and Grasby, 2014;Grasby et al, 2012;Hadgu et al, 2016;Ledésert and Hébert, 2012;Limberger et al, 2018;Majorowicz and Moore, 2014). The Western Canadian Sedimentary Basin and Williston Basin in the Canadian Prairies have the potential for sedimentary geothermal energy production (Jacek and Stephen, 2010;Majorowicz and Moore, 2014;Manz, 2011;Walsh, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the flow rate increases with the delay of simulation time due to matrix dissolution, which again exhibits exponential grow. On the whole, increasing attention has been significantly paid to geothermal development, and many scholars are studying the exploitation of a geothermal field from different aspects . The EGS test is extremely difficult and expensive before the construction of a power plant.…”
Section: Introductionmentioning
confidence: 99%